Online Learning from An Outreach Project Perspective: The Case of the Language Project of the Pacific Campus of UCR in the Context of Its Tenth Aniversary and the COVID-19 Pandemic - López-Montero, Rosberly (2021)
This paper tells about the change to virtual education due to the COVID-19 pandemic from the perspective of the outreach language project ED-2884 at the Pacific Regional Campus of the UCR. It presents the main challenges as well as opportunities derived from this health emergency towards its first decade of service in Costa Rican Central Pacific Region. Indeed, the abrupt change to online teaching has forced the project to rearrange the service offered to the community, but at the same time, it has allowed for a major geographic impact.